1998
DOI: 10.1177/0164027598202005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of For-Profit and Not-for-Profit Facility Status on the Quality of Care for Nursing Home Residents with Mental Illnesses

Abstract: This article examines whether a relationship exists between ownership status (for-profit and not-for-profit) of nursing homes and the quality of care for residents who are mentally ill. Rather than looking for an overall indicator of differences in quality between these ownership types, as other studies have done, three quality indicators are examined: structure, process, and outcome. Also, different types of nursing homes are examined by size and certification level. The authors fail to find consistent eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Internal organizational factors include size (Boyne, 2003;Moynihan & Pandey, 2005), network participation (Boyne, 2003;Harrington, Woolhandler, Mullan, Carrillo, & Himmelstein, 2001;O'Neill et al, 2003;Rainey & Steinbauer, 1999), human and monetary resources (Boyne, 2003;Brewer & Coleman, 2000), and the presence of organized resident groups. In addition, we control for a variety of environmental factors based on past research, including competition (Buchanan & Tullock, 1962;Castle & Shea, 1998;Milward & Provan, 2000;E. Ostrom, 1990;V.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Internal organizational factors include size (Boyne, 2003;Moynihan & Pandey, 2005), network participation (Boyne, 2003;Harrington, Woolhandler, Mullan, Carrillo, & Himmelstein, 2001;O'Neill et al, 2003;Rainey & Steinbauer, 1999), human and monetary resources (Boyne, 2003;Brewer & Coleman, 2000), and the presence of organized resident groups. In addition, we control for a variety of environmental factors based on past research, including competition (Buchanan & Tullock, 1962;Castle & Shea, 1998;Milward & Provan, 2000;E. Ostrom, 1990;V.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Many studies based on US data have concluded that nursing homes that run for profit are associated with lower quality of care (Steffen and Nystrom, 1997;Harrington et al, 2001Harrington et al, , 2002O'Neill et al, 2003;Amirkhanyan et al, 2008;Amirkhanyan, 2009). However, some studies have failed to find a significant relationship between running for profit and quality of care (Castle and Shea, 1998;Weisbrod and Schlessinger, 1986). Comondore et al (2009) have done a meta-analysis of such studies, and they suggest that, on average, not for-profit nursing homes have a trend towards higher quality of care than for-profit nursing homes, but for a large proportion of the studies, this trend is not significant.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to improve nursing home quality, many researchers have explored its determinants, such as staffing (Bostick, Rantz, Flesner, & Riggs, 2006;Bowblis, 2011;Kim et al, 2009;McDonald, Wagner, & Castle, 2013;Shin, 2013;Spilsbury, Hewitt, Stirk, & Bowman, 2011), nursing home report cards (Grabowski & Town, 2011;Mukamel, Weimer, Spector, Ladd, & Zinn, 2008;PesisKatz et al, 2013), ownership (Aaronson, Zinn, &Rosco, 1994;Castle & Shea, 1998;Grabowski, Feng, Hirth, Rahman, & Mor, 2013;Harrington, Woolhandler, Mullan, Carrillo, & Himmelstein, 2001;Stevenson, Bramson, & Grabowski, 2013;Worth, 2008), and market conditions (Bowblis, 2012;Starkey, Weech-Maldonado, & Mor, 2005;Zinn, 1994). In addition, the Centers for Medicare & Medicaid Services launched the Five-Star Quality Rating System in 2008, which provides information about health inspections, staffing, and quality and is consolidated in the Nursing Home Compare (NHC) database.…”
mentioning
confidence: 99%